2021
DOI: 10.1093/jnci/djab194
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Profiling and Response to CD19 Chimeric Antigen Receptor T-Cell Therapy in B-Cell Malignancies

Abstract: Background Chimeric antigen receptor (CAR) T-cells directed against CD19 (CART19) are effective in B-cell malignancies, but little is known about the molecular factors predicting clinical outcome of CART19 therapy. The increasingly recognized relevance of epigenetic changes in cancer immunology prompted us to determine the impact of the DNA methylation profiles of CART19 cells on the clinical course. Methods We recruited 114 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…At the molecular level, in addition to cell surface markers, some studies have identified indicators of response associated with CAR-T cell gene expression, CAR integration site, and its epigenetic regulation. Recently, our group described a DNA methylation signature in CAR-T cells that we named EPICART ( 79 ). EPICART, like a previously described gene expression signature ( 77 ), associates good outcome with a signature enriched in naïve-like or early memory cell populations, thus reinforcing the importance of the presence of these subsets at preinfusion to determine overall response.…”
Section: Biomarkers In Actmentioning
confidence: 99%
“…At the molecular level, in addition to cell surface markers, some studies have identified indicators of response associated with CAR-T cell gene expression, CAR integration site, and its epigenetic regulation. Recently, our group described a DNA methylation signature in CAR-T cells that we named EPICART ( 79 ). EPICART, like a previously described gene expression signature ( 77 ), associates good outcome with a signature enriched in naïve-like or early memory cell populations, thus reinforcing the importance of the presence of these subsets at preinfusion to determine overall response.…”
Section: Biomarkers In Actmentioning
confidence: 99%
“…A limitation of our work includes the relatively small number of diagnostic CSF specimens of inherently very small volumes and/or paucity of available cell number as well as the small number of patients. Our findings however emphasize the need for further systematic in-depth studies, using next generation single-cell RNA sequencing (scRNASeq), proteomics, and/or epigenetic analysis, 40,41 to reveal the precise transcriptional signature underlying the treatment-refractory state of individual T-cell clones. Possible mechanisms may include an acquired steroid-resistance due to altered JAK-STAT-pathway signaling, 42,43 upregulation of the glucocorticoid-induced TNF receptor family-related protein (GITR) expression, 44 and/or a previously observed chemo-resistance of certain central memory/memory stem T-cell subsets.…”
Section: Discussionmentioning
confidence: 91%
“…The T-cell methylation profiles of 157 patients with B-cell malignancies, including ALL and NHL, were downloaded from the GEO database under the accession number GSE179414 ( 22 ). The dataset comprised 77 ALL and 37 NHL cases, who were treated with CART19 cells.…”
Section: Methodsmentioning
confidence: 99%